2001
DOI: 10.1021/ja016324k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Solute Size and Solute−Water Attractive Interactions on Hydration Water Structure around Hydrophobic Solutes

Abstract: Using Monte Carlo simulations, we investigated the influence of solute size and solute-water attractive interactions on hydration water structure around spherical clusters of 1, 13, 57, 135, and 305 hexagonally close-packed methanes and the single hard-sphere (HS) solute analogues of these clusters. We obtain quantitative results on the density of water molecules in contact with the HS solutes as a function of solute size for HS radii between 3.25 and 16.45 A. Analysis of these results based on scaled-particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
222
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(242 citation statements)
references
References 43 publications
19
222
0
1
Order By: Relevance
“…The asymptotic approach to the macroscopic thermodynamic description with increasing solute size is consistent with the contact density profiles (19,24) (Fig. 2b).…”
Section: (D) Shown Is the Ratio P N͞supporting
confidence: 71%
See 2 more Smart Citations
“…The asymptotic approach to the macroscopic thermodynamic description with increasing solute size is consistent with the contact density profiles (19,24) (Fig. 2b).…”
Section: (D) Shown Is the Ratio P N͞supporting
confidence: 71%
“…For example, the blurring of the entropy convergence in thermal unfolding of proteins (21), the drying-induced collapse of hydrophobic polymers (22), or the strong association of nanoscopic solutes in water cannot be explained based on the physics of small-solute hydration alone. Independent molecular simulation studies of various model nanoscopic solutes in water have also reported dewetting of solute surfaces and the resultant strong water-mediated interactions between those solutes (20,(23)(24)(25)(26)(27).LCW theory predicts that the free energy of hydration of hard-sphere solutes increases approximately linearly with solute volume for small solutes, and with solute surface area for large solutes, and the small-to-large crossover occurs over nanoscopic lengthscales (28). The small-solute hydration is governed by microscopic density fluctuations (11,12,(16)(17)(18), whereas largesolute hydration is described by the thermodynamics of interface formation (1,15,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With increasing solute length scale, the elegant theory by Lum, Chandler, and Weeks (11) as well as computer simulations (12, 13) predict a gradual dewetting of the solute. Near large solutes or a hard-wall, water density is small and vapor-like, and the wall-water interface resembles a water vapor-liquid interface (14).Realistic solutes exert van der Waals and/or electrostatic interactions and pull the water interface closer, wetting the solute surface (12,(15)(16)(17)(18). The extent of wetting depends on the strength of attraction and on the local surface curvature or roughness.…”
mentioning
confidence: 99%
“…Realistic solutes exert van der Waals and/or electrostatic interactions and pull the water interface closer, wetting the solute surface (12,(15)(16)(17)(18). The extent of wetting depends on the strength of attraction and on the local surface curvature or roughness.…”
mentioning
confidence: 99%